Molten carbonates for advanced and sustainable energy applications: Part I. Revisiting molten carbonate properties from a sustainable viewpoint. (2nd November 2016) - Frangini, S.; Masi, A.
Abstract: In addition to the traditional fuel cell field, recent research on molten alkali carbonates is increasingly directed towards their use as efficient reaction medium or for the preparation of highly functional materials in advanced, low fossil-carbon and sustainable energy applications. The expansion of renewable energy use, and particularly of solar power, appears to be a major driving force behind the new wave of molten carbonate studies. However, since the relevant molten carbonate literature in the new field of sustainable energy is still relatively small, this work is an attempt to stimulate further and more systematic investigations on molten carbonates by revisiting some of their characteristic properties from a modern and sustainable perspective. In particular, this work is specifically focused on molten carbonate properties that are important for uses as electrolyte or reaction media. Specific properties that have been considered as major indicator of technological sustainability include safe melt chemistry, thermal and moisture stability, high electrical conductivity combined with low metallic corrosiveness, ease to regenerate, tunable acid-base and redox properties, and catalytic activity in gasification and partial oxidation reactions. From this analysis it can be concluded that molten carbonates are very stable systems under a wide range of chemical conditions and mild to moderate temperature ranges, giving the possibility of designing ideal reaction and electrolyte media for advanced chemical/electrochemical processes related to production, storage, conversion and efficient uses of renewable energy, particularly of solar energy, in future low-carbon energy scenarios. Highlights: Molten carbonate properties are reviewed using sustainable criteria. Molten carbonates ideal for mild-to-moderate temperature process applications. Molten carbonate processes for storage, conversion, efficient uses of solar energy.